Phosphodiesterase-3 inhibitor (cilostazol) attenuates oxidative stress-induced mitochondrial dysfunction in the heart - Siriporn C. Chattipakorn (2018)
Background: Cilostazol is a type 3 phosphodiesterase inhibitor which has been previously demonstrated to prevent the occurrence of tachyarrhythmia and improve defibrillation efficacy. However, the mechanism for this beneficial effect is still unclear. Since cardiac mitochondria have been shown to play a crucial role in fatal cardiac arrhythmias and that oxidative stress is one of the main contributors to arrhythmia generation, we tested the effects of cilostazol on cardiac mitochondria under severe oxidative stress. Methods: Mitochondria were isolated from rat hearts and treated with H2O2 to induce oxidative stress. Cilostazol, at various concentrations, was used to study its protective effects. Pharmacological interventions, including a mitochondrial permeability transition pore (mPTP) blocker, cyclosporine A (CsA), and an inner membrane anion channel (IMAC) blocker, 4'-chlorodiazepam (CDP), were used to investigate the mechanistic role of cilostazol on cardiac mitochondria. Cardiac mitochondrial reactive oxygen species (ROS) production, mitochondrial membrane potential change and mitochondrial swelling were determined as indicators of cardiac mitochondrial function. Results: Cilostazol preserved cardiac mitochondrial function when exposed to oxidative stress by preventing mitochondrial depolarization, mitochondrial swelling, and decreasing ROS production. Conclusions: Our findings suggest that cardioprotective effects of cilostazol reported previously could be due to its prevention of cardiac mitochondrial dysfunction caused by severe oxidative stress. ©2014 JGC All rights reserved.